The use of surfactant-based separation techniques for monitoring of orthophosphate in natural waters and wastewater - Katsaounos, Christos Z.; Giokas, Dimosthenis L.; Vlessidis, Athanasios G.; Paleologos, Evangelos K.; Karayannis, Miltiades I. (The Science of the total environment, 2003)
In an effort to monitor orthophosphate in natural waters and wastewater in the Ipirous region (Greece), an analytical methodology was established owing to the need for interference-free determination at the low mg/l levels. The method applied for the determination of orthophosphate is based on its reaction with molybdate towards a yellow heteropoly acid complex, which is electrically balanced with a cationic surfactant (cetylatrimethylammonium bromide) towards a complex non-polar derivative. This derivative is conveniently solubilized in the micelles of a non-ionic surfactant under mild conditions and measured spectrophotometrically at 370 nm after its uptake with a sulfuric acid—methanol solution. By simply preconcentrating 10 ml of sample volume a detection limit of 2.6 μM was obtained. Due to the required dilution step and signal enhancement caused by the presence of surfactant, interference from the presence of anionic species (mostly silicate and arsenate) was minor and could be conveniently alleviated by the use of tartaric acid and Na 2SO 3, respectively. The method was successfully applied to real samples obtained for the natural sites subject to the monitoring survey ranging in their matrix complexity from clean river water to wastewater.